Synthesis and antimicrobial activity of some novel N-substituted benzimidazoles - Gund, Dnyandev Radhu; Tripathi, Alok Pramod; Vaidya, Sanjay Dashrath (European Journal of Chemistry, 2017)
Synthesis of a series of new substituted benzimidazole derivatives by the condensation of o-phenylenediamine with urea to give 1,3-dihydro-benzimidazol-2-one which reacted with phosphoryl chloride to give 2-chloro-1H-benzimidazole is reported. The product was then alkylated at the benzimidazole NH with different electrophilic reagents leading to functionalized derivatives. Structures of the newly synthesized products have been deduced on the basis of spectral and analytical data. The synthesized compounds were screened for their antimicrobial activity. This exhibited some promising results towards testing organism in-vitro.